What Does Digitalization Offer to English for Specific Purposes Learning? : A Systematic Literature Review - Yunita, Sri; Susilawati, Susilawati; Darwis, Riadi; Ramadhan, Arrizqi (Jurnal Paedagogy, 2025)
This study aims to discover what digitalization offers to promote students' learning in ESP classrooms and the contributions of lecturer digital competency to student learning.  This study employed a systematic literature review with SALSA (Search, Appraisal, Systhesis, and Analysis) procedure and analyzed 15 article journals from Sinta and Scopus indexed journals to ensure credibility.  The data were analyzed using thematic analysis to identify patterns and categories related to digitalization in ESP learning. The findings suggest that digitalization in ESP classes offers several benefits for student learning including learning content accessibility, assignment efficiency, flexibility, engagement, interaction, motivation, academic skills, and performance improvement, and promoting some of the 21st-century skills. Lecturers’ digital competence is also trusted to contribute to students’ learning, covering instructional effectiveness, engagement, interaction, assessment, and motivation. To summarize this study, developing a supporting digital environment for higher education learning is strongly recommended by selecting appropriate digital tools, properly infusing the tools into the curriculum and learning with the caveat that all parties involved be adequately trained, and considering students' long-term engagement in the digital environment. Technology-related issues, such as bandwidth and student technological fatigue, deserve to be addressed.